The Maritime Human Resources Development Strategy In Indonesia (Literature Study) - Fazry, Rachma waty (Jurnal Kesehatan & Disiplin Ilmu, 2024)
The purpose of this study is to find and assess the main HR management strategies that can improve the performance of the maritime industry. The analysis results in a growth strategy, also known as a growth-oriented strategy. This strategy shows that the company has a strong condition and has the ability to continue to grow by utilizing existing opportunities to achieve the highest level of profit. achieve the highest level of profit. The calculation results show that this strategy is very profitable. The position in quadrant I has a weighted total score of strengths and weaknesses of 2.710504 and a weighted total score of opportunities of 2.653142.